Los hechos acerca de la fibra - Jennifer Hillan; R. Elaine Turner; Wendy J. Dahl (EDIS)
This 2-page fact sheet is the Spanish-language version of FCS8793/FY849: Facts About Fiber. Written by Jennifer Hillan, R. Elaine Turner, and Wendy J. Dahl. Published by the UF Department of Family Youth and Community Sciences, May 2011.